Pravastatin plus L-arginine prevents adverse pregnancy outcomes in women with uteroplacental vascular dysfunction - Aleksandar Jurisic (17052408) (2021)
Background Uteroplacental vascular dysfunction, characterized by diminished uterine artery (UtA) blood flow in the second trimester is a clinically useful predictor of the further development of preeclampsia, fetal growth restriction and stillbirth. Efforts to develop effective treatments to protect pregnancies with abnormal UtA Dopplers would be of significant clinical benefit for mothers and their fetuses. Objective The aim of this pilot non randomized control study was to use pravastatin +L-arginine to improve uteroplacental haemodynamics and prevent adverse maternal and neonatal outcomes in women with abnormal Dopplers and high risk for developing adverse pregnancy outcomes. Study design This study was performed between 2015 and 2018. All women received primary care at OB/GYN Polyclinic Jurisic and Narodni Front University Hospital, University of Belgrade Medical School, Serbia. Approval for investigational drug use was obtained and all women gave informed consent. 10 pregnant women with a poor obstetric history that developed uteroplacental dysfunction (UtA pulsatility index (PI) above the 95th percentile and notching) at 20.5 weeks IQR [17.7–22] gave consent to be treated daily with pravastatin (40 mg) and L-arginine (1.5 g) to improve placental blood flow and pregnancy outcomes. 5 women remained untreated after diagnosis at 21 weeks [20−22] (control group). Due to presence of risk factors for pregnancy complications, close maternal and fetal monitoring was undertaken in all patients. Doppler examinations were performed to monitor changes in placental vascular resistance and fetal well-being and growth. Results PRAV+L-arginine improved uteroplacental haemodynamics, increased fetal growth and prevented early onset preeclampsia leading to delivery close to term (delivery date: median 38 weeks, IQR[36.5–39]) and appropriate weight for gestational age compared to controls, in which placental blood flow did not improve and 2 women developed severe early onset preeclampsia. Neonates from the control group were born preterm (25 weeks IQR[23.5–25]), growth restricted and spent several months at NICU. Two neonates died due to prematurity-associated complications. PRAV+L-arginine treatment prolonged pregnancies for 4.1 months, compared to 26 days in the untreated group, preventing neonatal complications associated with prematurity. The infants are now 1–3 years old and show normal growth and development. Conclusion This study describes the successful management with pravastatin+L-arginine of 10 pregnant patients with uteroplacental vascular dysfunction and high risk of adverse maternal and fetal outcomes. A larger study is being organized to confirm these observations. Other Information Published in: Vascular Pharmacology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.vph.2020.106824